Orphans cannot be after-birth aborted: a response to Bobier - Singh, Prabhpal (Journal of medical ethics, 2023)
I offer a response to an objection to my account of the moral difference between fetuses and newborns, an account that seeks to address an analogy between abortion and infanticide, which is based on the apparent equality of moral value of fetuses and newborns.